Situating the Scientist: Creating Inclusive Science Communication Through Equity Framing and Environmental Justice - Polk, Emily; Diver, Sibyl (Frontiers in Communication, 2020)
This article draws on environmental justice (EJ) scholarship to develop a novel concept of equity framing that can be used to achieve more inclusive science communication. We argue that centering equity in our communications framing can provide an essential point of access for marginalized communities to engage with scientific communication, and also an important opportunity for scientific researchers and writers to become more accountable to disadvantaged communities. Viewing science communication through an equity lens asks communicators to not only frame science in ways that are salient to particular audiences, but it also asks communicators to attend to particular discriminatory historical practices that have targeted marginalized communities, and continue to do so through current scientific discourse. EJ strategies for equity framing include asking science communicators to (1) become aware of their own positionality and partial perspectives, (2) name sources of inequity that arise from uneven power relations, and (3) find intersections with initiatives that are rooted in the experiences of disadvantaged communities. To ground our approach to equity framing, we also present our experiences teaching Stanford University's first comprehensive class on environmental justice as a case study. Key outcomes included: adding missing perspectives to scientific knowledge production by inviting representatives from diverse and marginalized communities to teach us; increasing the social relevance of scientific findings by asking our students to center the concerns and insights of marginalized communities in their communication; and encouraging collective action to address equity concerns and achieve a healthier society for all.